Nostalgia: Suggestioni derridiane - Spatola, Beatrice (B@belonline, 2021)
In the current cultural landscape, Italian theory seems to have replaced French theory, biopolitics seems to have replaced sovereignty, life is said to have replaced death. In reality, following Derrida and his deconstruction, this is not the case; sovereignty is something ineliminable, arch-original and irreducibly nostalgic. It is a nostalgic sovereignty that in the only viable form, the one of reasonable democracy, discovers its vulnerability in the expectation of the other.